Kajian Sifat Fisikokimia Permen Jelly oleh Tiga Varietas Jahe (Zingiber officinale) dan Perbedaan Konsentrasi Ekstrak Karagenan dari Rumput Laut (Eucheuma cottoni) - Mochammad Arif Saputra; Noor Harini; Rista Anggriani (Food Technology and Halal Science Journal, 2020)
Ginger is one type of medicinal plants and spice, which has been known by the Indonesian people. Usefulness of ginger suchas for seasoning, mixed food/drink, medicines and cosmetics. Ginger has a distinctive aroma due to essential oil content and a specific flavor that is spicy derived from oleoresin compounds. Consumption continuously is excellent for health. Ginger has a spicy flavor is difficult to fresh, it needs to be inovaded. In this research ginger is processed into jelly candy. Jelly candies require a gel-forming material to form a chewy texture. In this research, the gel-forming material is used in the Caragenan. The Caragenan is exported using a solution of KOH 10%. This research aims to determine the effect of ginger varieties against the brightness of jelly candies, antioxidants, flavors and aromas, knowing the influence of the addition. The research was conducted in two phases. The first phase of the extraction of carrageenan from seaweed Euchema cottoni used a solution of KOH 10%. Caragenan extract is further analyzed for yield, moisture content, viscosity and gel strength. The second stage was making ginger jelly candy production with difference of caragenan concentration using nest design (Nested). The parent factor of three varieties of ginger is ginger elephant, red ginger and ginger emprit, while the concentration of caragenan, 7 grams, 8 grams and 9 grams. The analyzed parameters were water content, water content, sugar reduction, antioxidant, texture, color , pH and organoleptic (texture, aroma, color and flavor). The results showed that three varietas of ginger affect the brightness of jelly sweets, antioxidants, flavors and aromas. Best was results obtained at the treatment of Ginger Javanese with the addition of a 9 g caragenan with 82.331% of antioxidant activity, 4.835 N of texture, 13.132% of water content, 4.9 (strong) of organoleptic Aroma, 4.5 (supple) of organoleptic texture, and 4.6 (spicy) of flavor.